THE EFFECT OF EXTRACTION METHOD ON FATTY ACID PROFILE OF TRADITIONALLY AND MECHANICALLY EXTRACTED SHEA BUTTER SAMPLES FROM NASARAWA STATE - Abu, Abigail J.; Muhammad, Faruruwa Dahiru; Awe, Femi Emmanual (FUDMA JOURNAL OF SCIENCES, 2025)
Shea butter, a valuable plant fat has been extracted from the nuts of Shea tree. This study aim at determining the effect of extraction method on fatty acid profile of Shea butter samples from four local government areas of Nasarawa state, namely: Akwanga, Kokona, Nasarawa and Lafia. Two different methods were used for the extraction, which were the traditional and mechanical methods. The fatty acid profiles where analyzed using Gas Chromatography-Mass Spectroscopic (GC-MS) analytical method. The results obtained for fatty acid profile for the two extract varies. The butter extracted with the tradition method project three fatty acids which were oleic acid, ethyle oleate, and behehic acid while that of the mechanical methods detected seven fatty acids which were oleic acid, ethyl oleate, stearic acid, palmitic acid, linoleic acid, myristic acid, and pentadecanioc acid. While the traditional method project majorly oleic acid and its esters, the mechanical methods shows more of the fatty acids and their esters. The results of fatty acids profile therefore shows that, the traditional methods used in these region of Nasarawa state for the extraction of shea butter do not release all the fatty acids in the extracts and needs to be modernized so as to obtain shea butter of best quality.